Performance of improved decode-and-forward cooperation in low SNR - ZHU Yi-jun; LI Ying; TIAN Zhong-jun; CHEN Jin-yang (Tongxin xuebao)
An enhancement was proposed that the receiving node feeds back its decoding state to the other nodes.Further,the enhancement can improve the performance of decode-and-forward cooperative diversity.The outage probability and throughput of incremental relay and selection relay were derived in low SNR,and the three-order approximation of out-age probability was presented.Combined with the strong points of incremental relay and selection relay,joint relay was brought forward.The theoretical analysis and numerical simulation reveal that the proposed joint relay has such pre-dominant performances as outage probability and throughput.